ANALISIS FAKTOR DETERMINAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS JATIKALEN KABUPATEN NGANJUK - Siti Nur Farida; Dwi Retno Wati (Library Unit of the College of Health Science Husada Jombang, 2023)
Introduction: Anemia of pregnancy is a national problem faced by the Indonesian government because it shows the value of the socio-economic welfare of the community and affects the quality of human resources. Apart from that, anemia in pregnant women can be said to be